Isolated REM sleep behavior disorder is associated with altered 24-h rest-activity measures - Winer, Joseph R.; Lok, Renske; Ekelmans, Adrian; Bueno, Flavia; Poston, Kathleen L.; Zeitzer, Jamie M.; During, Emmanuel H. (Frontiers in Sleep, 2023)
Introduction Isolated REM sleep behavior disorder (iRBD), the loss of motor inhibition during REM sleep, is a symptom of prodromal Lewy body disease, with over 80% of iRBD patients progressing to Parkinson’s disease or dementia with Lewy bodies. Disruption of rest-activity patterns, an established predictor of Parkinson’s disease, has not been well characterized in patients with iRBD. Here, we tested the hypothesis that accelerometer-based measures of 24-hour activity would indicate greater fragmentation and variability in patients with iRBD relative to matched healthy controls. Materials and Methods Patients with iRBD (N=38) had 24-hour activity monitored for (mean ± SD) 24.6 ± 8.8 days using an Axivity wrist-worn accelerometer. Age, sex, and body mass index matched healthy older adults (N=119) were selected as controls. Raw accelerometer data were processed and nonparametric and cosinor measures of 24-hour activity were calculated. Functional principal component analyses (fPCA) were applied to detect differences in 24-hour activity patterns. Results Compared to matched controls, individuals with iRBD had significantly lower cosine amplitude, mesor, and activity during their most active 10 hours, reflecting overall lower levels of activity and disrupted activity. They also had significantly increased movement during the night (L5). FPCA indicated that decreased daytime and increased nighttime activity may explain overall differences observed in iRBD. Conclusion Multiple metrics of rest-activity rhythms support the hypothesis that 24-hour activity measures are altered in iRBD. This dysfunction may reflect degeneration of sleep-wake regulating circuits, representing a symptom of iRBD and indicating the early stages of Lewy body disease.